Oral corticosteroids during pregnancy and offspring risk of congenital heart defects: a nationwide cohort study. (19th October 2019) - Schmidt, Amalie Bøggild; Lund, Marie; Corn, Giulia; Øyen, Nina; Wohlfahrt, Jan; Melbye, Mads
Abstract: Background: Pre-pregnancy diabetes is a strong risk factor for congenital heart defects (CHDs), suggesting a role for glucose in the causal pathway. Oral corticosteroids may cause hyperglycemia and maternal use could affect embryonic heart development. The objective of this study was to determine the association between maternal intake of oral corticosteroids 0–8 weeks after conception and CHDs in offspring. Methods: A register-based nationwide prevalence study including all live singleton births in Denmark, 1996–2016, was conducted. In total, 1 194 687 individuals and their mothers were identified and linked with information on offspring CHDs and the mothers' use of oral corticosteroids in early pregnancy. Corticosteroid use was defined as a filled prescription for maternal use of oral corticosteroid 0–8 weeks after conception. CHDs were identified through International Classification of Diseases codes. The association was estimated by prevalence (odds) ratios using logistic regression and propensity score-matched analyses. Results: Among 1 194 687 live births, 2032 had a mother who had used oral corticosteroids 0–8 weeks from conception. Of these offspring, 32 had a heart defect. Among the offspring of never-users of oral corticosteroids, 10 534 had a heart defect. The adjusted prevalence ratio was 1.29 (95% confidence interval, 0.90–1.84) comparing offspring prevalence of heart defects in oral corticosteroid users with that in oral corticosteroid never-users. Propensity score-matched analysis yielded similar results (prevalence ratio 1.38; 95% confidence interval, 0.95–2.02). Conclusions: This study supports that there is no association between maternal use of oral corticosteroids in the first 8 weeks after conception and CHDs.